-16=-3(6k+9)

Simple and best practice solution for -16=-3(6k+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=-3(6k+9) equation:


Simplifying
-16 = -3(6k + 9)

Reorder the terms:
-16 = -3(9 + 6k)
-16 = (9 * -3 + 6k * -3)
-16 = (-27 + -18k)

Solving
-16 = -27 + -18k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '18k' to each side of the equation.
-16 + 18k = -27 + -18k + 18k

Combine like terms: -18k + 18k = 0
-16 + 18k = -27 + 0
-16 + 18k = -27

Add '16' to each side of the equation.
-16 + 16 + 18k = -27 + 16

Combine like terms: -16 + 16 = 0
0 + 18k = -27 + 16
18k = -27 + 16

Combine like terms: -27 + 16 = -11
18k = -11

Divide each side by '18'.
k = -0.6111111111

Simplifying
k = -0.6111111111

See similar equations:

| 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x | | 3(c-2)+8=6+c-4 | | 3x+1=3x+0 | | 2x+3y=155 | | 9.8.2x=96 | | 2z-6z=-25 | | 20=22-d | | -7(9-5a)=-23 | | 3p.9=24 | | -4+3(18-9m)= | | x(x+4)+28=(x-1)(x+8) | | 5=6p-1 | | 2x(3x+x^2)-2x^2=136 |

Equations solver categories